Caracterización química y degradabilidad in situ del rastrojo de maíz (Zea mays L.) en los cantones Pindal, Celica y Zapotillo de la provincia de Loja. - Curay Jumbo, Israel Manuel (2018)
In the present investigation the chemical composition and degradability textit in situ of maize stubble ( textit Zea mays L.) were evaluated in the cantons of Celica, Pindal and Zapotillo of the province of Loja. The work was divided into two phases: field and laboratory, in the field phase, the collection of samples of the maize stubble and DK7088 from the study area was carried out; In the laboratory phase, the chemi- cal analysis and digestibility textit in situ was carried out, in the Laboratory of Soils, Waters and Bromatology, and in the fifth Punzara experiment belonging to the Na- tional University of Loja. The sample size was made by a random non-probabilistic sampling, where the producers were divided into groups or conglomerates according to the area of highest corn production, collecting a sample of 1000 g of each variety of corn stubble, including stem, leaves and panca. In the chemical composition, the following variables were determined: dry matter (DM), ash (Cz), protein (PB) and crude fiber (FC); in the digestibility textit in situ, the degradability of the dry matter was identified and the metabolizable energy was evaluated based on the dry matter digestibility of the time 48 h. For the study of the variables, an analysis of varian- ce was carried out, where the fixed variables were the origin, the variety and their interaction; Likewise, to obtain the difference between the means of the treatments, the Tukey test was applied with a probability of 5 %, applying the procedures of the linear models Generalized Linear Models (GLM) and Mixed linear model (MIXED). In the chemical composition, there was a significant difference in DM with a p-value of (p = 0.02) for provenance and (p = 0.03) in the interaction, due to the degree of humidity that the sample presented when it was collected. . Regarding the degrada- bility, it was possible to determine that the most degradable stubbles are found in Celica in the variety DK7088 with 31.20 % and in Pindal in the variety criolla with 31.35 % being its fraction insoluble but potentially degradable (b) more degradable, compared to the other fractions of corn stubble. Regarding the metabolizable energy, the highest values were presented in Celica, in the variety DK7088 with an average of 1.35 Mcal / Kg and in the Creole 1.22 Mcal / Kg. No significant difference was found in each variety, but in terms of provenance if significant difference was found (p = 0.0003), obtaining the values of 1.29 Mcal / kg DM in Celica, 1.04 Mcal / kg DM in Pindal and 0.97 Mcal / kg of MS in Zapotillo. Key words: corn stover, degradation, In situ, Dry matter.